Servant leadership towards career success: An Islamic approach - Zaman, Farhana; Hashim, Junaidah; Osman-Gani, AAhad M. ((UiTM Press), Universiti Teknologi MARA Cawangan Pahang, 2016)
The purpose of this exploratory research is to develop an Islamic approach for career success for Muslim mangers through servant leadership. The theoretical foundation of this study is based on spillover theory. The extensive review of career literature showed that the Western secular approach for career success is found to be dominant for various reasons. However, as Muslims want to be successful in this life and in the hereafter, it is more appreciable if they can follow an Islamic approach. As Islam makes everyone shepherd and answerable with regard to his flock, it is actually reinstating the practice of servant leadership, the humanistic and spiritual way of management. In Islam, servant leader is a person who makes efforts to be useful to his customers. This requires every Muslim to emphasize five key parameters of Islamic practice: justice, trust, righteousness, the struggle within oneself towards selfimprovement, and promise-keeping. Greenleaf recently reintroduced this Islamic leadership concept saying “The servant leader is servant first. It begins with the natural feeling that one wants to serve….”. This concept is having huge attention in the Western society. The present study is exploratory and based on a literature review. It identifies how Muslim managers are applying servant leadership approach to observe their career success. It also outlines potential key factors.